The faces of holiness. Jesuit martyrs and founders on the tiles of the sacristy of “San Pedro de Lima” - Pedrosa Velasco, Dionicia Lizbeth (2022)
This article seeks to determine the origin of the artistic sources that would have served as inspiration for the realization of the portraits of the holy martyrs and Jesuit founders reflected in the medallions or cartouches on the tiles of the sacristy of the old Colegio Máximo de San Pablo (currently San Pedro de Lima). Although there are studies that have established European engravings as a source of viceroyalty painting in Lima from the 17th and 18th centuries, no study has been carried out in relation to the origin of the images of the aforementioned sacristy. Likewise, it is intended to specify that the meaning of the characters in the tile medallions would represent an ideal of life for the Jesuit, as well as a reminder of the sacrifices that must be made to fulfill the evangelizing ideal of the order. With this repertoire of its own saints, the nascent Jesuit order affirmed itself with its own saints in relation to other religious orders. Additionally, the analysis of the images of the saints represented on the tiles will contribute to hagiographic studies of the Society of Jesus, since San Pedro de Lima contains the most extensive Jesuit collection of these images in South America.